Slovenski učni načrt za predmet likovna umetnost v gimnazijskem programu v primerjavi s podobnimi dokumenti evropskih držav - Zupančič, Tomaž (Revija za elementarno izobraževanje, 2015)
Slovenian Secondary School Visual Arts Curriculum in Comparison with Similar European Documents. Political changes in Slovenia in the early 1990s were followed by changes to the educational system. As regards the professional field, the last thirty years have seen major changes to teaching art all around the globe and also in Slovenia in the sense of the so-called postmodern visual arts curriculum. Slovenian art curricula are facing similar problems as the curricula in other countries. By comparing Slovenian art curricula for secondary school with those in seven different countries (Croatia, Estonia, Finland, Ireland, Latvia, Norway, and Spain), we wished to shed light on the Slovenian curriculum in a broader context. The Slovenian curriculum and those of other countries have been scrutinised and juxtaposed from different viewpoints. It has been established that Slovenian course syllabi have individual characteristics in common with the countries compared. The placement of art education into the timetable is similar to that in other countries. In Slovenia and in all the other countries, art education is a compulsory subject but with a different amount of taught time. The documents show differences as regards their structure, the terminology in the classification of the fields of visual arts, the implementation of contemporary content, multiculturalism, and sustainability. The comparison has shown that the Slovenian national curriculum for gimnazija has a modern design in specific segments, while it could be better in others.
Keywords: art education; arts curriculum; secondary school; contemporary art; multiculturalism